HEC-RAS modeling for the determination of highest water mark as the reference surface for delineation of riparian reserve: Case Study of Nairobi River-Kenya - Malachi Odongo; Prof. Caleb Mireri; Dr. Patricia Mwangu (African Journal on Land Policy and Geospatial Sciences)
Context and background The importance of mangroves forest is undeniable especially in the coastal regions of Kenya. It’s the hub of ecological and socio-economic well-being, provision of protection against shoreline erosion, biodiversity support and contributes immensely to the livelihoods of the local communities. Nevertheless, the ecosystem encounters significant threats such as deforestation, pollution and climate change which compromise their sustainability and the livelihoods of the local communities. This study focused on mapping and developing a zonation strategy for the mangrove ecosystems of Mida Creek, Kilifi County in Kenya using Geographic Information Systems (GIS). The aim was to identify areas for restoration, conservation, and sustainable use based on the health of mangrove vegetation. The study employed remote sensing techniques such as Normalized Difference Vegetation Index (NDVI) and Vegetation Condition Index (VCI) to assess the health of mangrove forests. Goal and Objectives: The study aimed at utilization of geospatial technologies to come up with a mangrove map zonation. This was done by considering various factors to designate areas for restoration, conservation, and sustainable utilization of Mida Creek mangrove forest in Kilifi County. Methodology: The study utilized Landsat imageries for 2018 and 2024 which were sourced from USGS, it also deployed Mida Creek Shapefile from Regional Centre of Excellence (RCoE). ArcGIS pro. was used for the spatial analysis and visualization of Mida Creek’s zonation. Results: The study results revealed that 18.4% of the mangrove forest requires intervention because it has completely depleted, 23.6% of mangrove forest needs conservation it is unhealthy and the largest segment 58.0%, indicates regions deemed safe for sustainable utilization. These proportions give insight into the balance between human impact and natural preservation within Mida Creek's ecosystem.